Implementasi Media Gambar dalam Pembelajaran Tematik Integratif pada Siswa Kelas I di MIN 1 Jombang Tahun Ajaran 2018-2019 - siti aminah (Jurnal Al-Muta`aliyah : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2020)
Based on observations at MIN 1 Jombang, class I student learning achievement towards Thematic Integrative learning is relatively declining, because in the learning process the teacher only uses the lecture method. In this research, the study is directed at the use of picture media in learning. The focus of the problem in this study is the implementation of the use of image media in Thematic Learning, the difficulty factor of Integrative Thematic Learning of students in Class I MIN 1 Jombang, and the efforts of teachers in overcoming student learning difficulties in Class I MIN 1 Jombang. This research uses a qualitative approach. The process of collecting data, researchers use the method of observation, interviews, and documentation. The steps of this research procedure are data reduction, data display, data coding, data interpretation, and drawing data conclusions. The results obtained are (1) Implementation of picture media in thematic learning, namely: preparing images in accordance with the material and showing pictures during the learning process, (2) The factors of difficulty in Integrative thematic learning are: (a) Limited knowledge and teacher ability; (b) The teaching materials available still use the subject approach; (c) thematic teaching materials are still national in nature (d) supporting facilities that do not meet the requirements; (e) Schedules using subjects. (3) Efforts to overcome student learning difficulties in Thematic subjects at MIN 1 Jombang are repeating subject matter and providing exercises or assignments.